(untitled) (Revista de Artes Marciales Asiáticas, 2017)
Introduction: After the signing of the alliance among Japan, Germany and Italy’s governments in September 1940, several journals arose in order to spread the Japanese culture among people who knew very little about Italy’s new allied. Some documentaries also had the same function. Methods: The numerous textual and iconographical references concerning the Japanese warriors’ anthropology published in some Italian magazines during the 1940s have been compared, as well as to the few Italian monographs on the same theme and to some documentaries by Istituto Nazionale Luce, government propaganda organ. This subject has also been compared to the first Italian cultural production, concerning Japan, which dated back to the first decades of the 20th century. Moreover different intellectuals’ biographies of those times have been deeply analyzed. Results: Comparing to each other the anthropological references about Japan in the Italian cultural production during the Second World War, we can notice a significant ideological homogeneity. This can be explained through their writers’ common sharing of the militaristic, hierarchical and totalitarian doctrine of the Fascist Regime. The Fascist ideology can be summarized in the Bushido concept, as Inazo Nitobe defined it in 1916. This concept was already known in Italy on the early 20th century, far before Fascism. Discussions and conclusions: We can see how Italian perception of the Japanese anthropology on the early 20th century didn’t change over time and how its features will re-appear in the 40s under the influence of the Italian-Japanese coalition. So, Bushido became the essence of the Japanese military and national identity that Fascist Italy took as example for mass education. Some of these stereotypes will re-appear after the war and until recent times in popular culture and in mass perception of Japanese martial arts.